MODEL KOMUNIKASI PENANGGULANGAN BENCANA - Muhammad Hilmy Aziz (Kinesik, 2023)
Indonesia is located where the four main plates of the world meet, namely Eurasia, Indo-Australia, the Philippines, and the Pacific, which geologically makes Indonesia prone to earthquakes, tsunamis, and volcanic eruptions. This research provides a concrete picture of the latest communication models in disaster management studies that have been carried out still within the risk reduction paradigm. Preparing this communication model is expected to provide strategic potential as an effort and step where Indonesia can make organized disaster management at the communication level. This research uses a qualitative method which can give a concrete picture of how to handle disasters. In addition, FGD (Focus Group Discussion) is a way of collecting data through direct discussion and analyzing problems with experts. The research focuses on more than just the communication model as an essential part of disaster management. The development of literacy as a role model can be applied to form a sophisticated handling of disasters that integrates technology with society and media independence in presenting the information. Through these steps, disaster management can be realized in the communication corridor used to provide a new paradigm related to disaster management.